Arbitral award in face of the new alterations to the brazilian code of civil procedure and its impugnation in cases of absence A sentença arbitral frente às novas alterações do código de processo civil brasileiro e sua impugnação nos casos de inexistência - Rozane da Rosa Cachapuz; Márcia dos Santos Eiras (Scientia Iuris, 2009)
The present paper addresses the way in which the concept of sentence currently adopted by the Code of Civil Procedure alters the structure of the procedural system in which Law 9.307/96 was formed, enabling the possibility of utilizing new ways of ruling, amongst them the partial award and its impugnation, considering the prospect of utilizing an action of declaratory nature towards this end in cases where it happens to have no legal validity. O presente trabalho tem por escopo abordar a forma pela qual o conceito de sentença adotado atualmente pelo Código de Processo Civil altera a estrutura da sistemática processual em que foi moldada a Lei 9.307/96, abrindo possibilidade de utilização de novas modalidades de sentença, entre elas a parcial, sua impugnação, aí inclusa a utilização de ação de natureza declaratória para este fim.